Nghiên cứu phân lập thành phần và hoạt tính của các cucuminoit trích từ củ nghệ vàng (Curcuma longa L.). - Anh, Phạm Thị Hoàng; Tiến, Lê Xuân; Phượng, Nguyễn Thị Mạc; Hoa, Trần Thị Việt; Sung, Trần Văn; Nam, Phan Thanh Sơn (Vietnam Journal of Chemistry, 2012)
Curcuminoid extracted from yellow turmeric is a mixture of 3 constituents: curcumin, demethoxycurcumin (DMC) and bis-demethoxycurcumin (BDMC). Previous published papers mainly concentrated on the biological activities of curcuminoid mixture. In this work, we have separated three constituents of curcuminoid, characterized and comparatively studied antioxidant, antibacterial and cytotoxic acvitities of these curcuminoids. Curcumin exhibited stronger DPPH scavenging activity (IC50 = 55.083) than the mixture, DMC, BDMC and the reference antioxidant, trolox. Meanwhile, the mixture showed the antibacterial property against Staphylococcus aureus (MIC = 62.5 mg/ml) better than each components. The mixture and its three constituents also demonstrated good abilities in suppressing the proliferation of Hep-G2 and RD cell-lines.